2010
DOI: 10.1074/jbc.m109.080200
|View full text |Cite
|
Sign up to set email alerts
|

Cbl-b Is a Novel Physiologic Regulator of Glycoprotein VI-dependent Platelet Activation

Abstract: Platelet activation by newly exposed basement membrane collagen is a key initial step in both hemostasis and thrombosis (1). The complex of glycoprotein VI (GPVI) 2 and the Fc receptor ␥-chain is primarily responsible for activation of platelets by collagen (2). This receptor acts via a PLC␥2-dependent pathway, leading to generation of autocoids that recruit additional platelets to the site of injury. Signaling downstream of the GPVI/Fc receptor ␥ chain is similar to signaling initiated by activation of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…Although we confirmed the hyperphosphorylation of Syk in c-Cbl deficient platelets, phosphorylation of Akt was not significantly increased, indicating that c-Cbl does not target the PI3K pathway to limit platelet activation by GPVI. Platelets also express Cbl-b, a second member of the Cbl family, that, in differently to c-Cbl, has been implicated in GPVI-mediated platelets activation [32]. The antibody used in the present study is specific for c-Cbl as indicated in the data sheet, and thus whether or not Cbl-b may contribute to PI3Kβ activation and Akt phosphorylation by GPVI or by integrin α2β1 remains to be established.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although we confirmed the hyperphosphorylation of Syk in c-Cbl deficient platelets, phosphorylation of Akt was not significantly increased, indicating that c-Cbl does not target the PI3K pathway to limit platelet activation by GPVI. Platelets also express Cbl-b, a second member of the Cbl family, that, in differently to c-Cbl, has been implicated in GPVI-mediated platelets activation [32]. The antibody used in the present study is specific for c-Cbl as indicated in the data sheet, and thus whether or not Cbl-b may contribute to PI3Kβ activation and Akt phosphorylation by GPVI or by integrin α2β1 remains to be established.…”
Section: Discussionmentioning
confidence: 96%
“…Activated growth factor receptors, cytosolic tyrosine kinases, as well as phosphorylated adaptor proteins can interact with p85 and cause the activation of p110 catalytic subunit [14]. Among these, the adaptor protein c-Cbl is a known binding partner and activator of PI3K [29][30][31][32][33][34], and has been shown to associate with PI3K in integrin αIIbβ3 outside-in signaling, and to be tyrosine phosphorylated by Pyk2 (15). Here we demonstrated that upon integrin α2β1 engagement c-Cbl interacts with PI3K but is not tyrosine-phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Flow Cytometry-Washed murine platelets were used to measure the agonist-dependent level of activated ␣IIb␤3 receptors with phycoerythrin-conjugated antibody JON/A and the surface exposure of P-selectin with FITC-conjugated anti-Pselectin antibody as described previously (29). All determinations were performed on a FACSCalibur flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…After protein determination (BCA protein assay kit, Thermo Scientific), 40-80 g of total cell lysate was electrophoresed on 8% SDS-PAGE gels. Proteins were transferred to a PDVF membrane (Millipore Corp), subjected to Western blotting, 30 blocked for 1 hour with odyssey blocking buffer and incubated with the appropriate antibody 1:500 (vol/vol) in odyssey blocking buffer with 0.1% (vol/vol) Tween 20 (16 hours, 4°C). After washing, membranes were incubated with the appropriate LICOR secondary antibody (1 hour, 4°C).…”
Section: Protein Tyrosine Phosphorylationmentioning
confidence: 99%